Reversal by trypsin of the inhibition of active transport by colicin E1. - Dankert, J (1980)
The time course for inhibition of proline transport and irreversible loss of cell viability after treatment with colicin E1 was measured as a function of temperature between 13 and 33 degrees C, using a thermostatted flow dialysis system. Complete inhibition of proline transport at 33 and 13 degrees C occurred in 0.5 min and 3 to 5 min, respectively, after addition of colicin E1 at an effective multiplicity of about 4. At these times, the fractional cell survival, assayed by dilution directly from the flow dialysis vessel into trypsin, ranged from 35 to 80%, with viability always greater than 50% at the lower incubation temperatures. Further studies were carried out at 15 degrees C. Complete inhibition of proline transport, which required 2 to 3 min, occurred much more rapidly at 15 degrees C than did the decay of trypsin rescue, which required 10 to 15 min to reach a survival level of 10 to 20%. The direct addition of trypsin to the flow dialysis vessel, after an addition of colicin E1 that caused complete inhibition of proline or glutamine transport, resulted in restoration of net transport. The restored level was typically about 40% of the control rate, and was very similar to the fractional cell viability measured after incubation in trypsin in the same vessel. It is concluded that trypsin can restore active transport to a significant fraction of a cell population in which transport has been initially inhibited by colicin E1.